Towards triptycene functionalization and triptycene-linked porphyrin arrays - Senge, Mathias (My University, 2020)
Herein, 9,10-diethynyltriptycene is investigated for its use as a rigid isolating unit in the synthesis of multichromophoric arrays. Sonogashira cross-coupling conditions are utilized to attach various porphyrins and boron dipyrromethenes (BODIPYs) to the triptycene scaffold. While there are previous examples of triptycene porphyrin complexes, this work reports the first example of a linearly connected porphyrin dimer, linked through the bridgehead carbons of triptycene. Symmetric and unsymmetric examples of these complexes are demonstrated and single crystal X-ray analysis of an unsymmetrically substituted porphyrin dimer highlights the evident linearity in these systems. Moreover, initial UV–vis and fluorescence studies show the promise of triptycene as a linker for electron transfer studies, showcasing its isolating nature.
Keywords: BODIPYs; 9,10-diethynyltriptycene; multichromophoric arrays; Porphyrins; BODIPYs; 9,10-diethynyltriptycene; multichromophoric arrays